Revolution and Transition Cultural Policy in Bulgaria, 1989-2012 - Alexandrov, Alexandar (LIT Verlag GmbH & Co. KG, 2017)
Bulgaria's cultural policy has experienced many transformations since the revolution. One of the most important is that at the beginning the conviction developed that those elements which could not support themselves because of the new market situation made no relevant social contribution. One of the aims of this thesis is to question what the reality of "cultural economy" is and how this is reflected in law-making and life.